Answer:
13
Step-by-step explanation:
We have the following expression:
[tex]8^{\frac{2}{3} } -\sqrt{9}*10^{0} + (\frac{1}{144}) ^{-\frac{1}{2} }[/tex]
If we do part by part, we have remains:
[tex]8^{\frac{2}{3} }[/tex] = 4
8 = 2^3
Therefore, the exponents 3 * 2/3 = 2 are multiplied
2^2 = 4
[tex]\sqrt{9}*10^{0}[/tex] = 3
We know that the root of 9 is equal to 3 and that every number raised to 0 is equal to 1, therefore 1 * 3 = 3
[tex](\frac{1}{144}) ^{-\frac{1}{2} }[/tex] = 12
When the exponent is negative, the fraction can be inverted and at the end there is 144 ^ 1/2, which would be the root of 144, which is equal to 12.
So, we have:
4 - 3 + 12 = 13